2021
DOI: 10.46328/ijonses.124
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pre-service Elementary Science Teachers’ Science Teaching Efficacy Beliefs through Microteaching by Promoting Efficacy Sources

Abstract: Science teaching efficacy belief (STEB) is of paramount importance as it motivates teachers to teach science or hinders them from teaching science. Pre-service teachers' efficacy beliefs may change during their method courses. Knowing how pre-service teachers' beliefs change over time can significantly contribute to teacher educators to improve teacher efficacy. This study examined the effect of microteaching on pre-service elementary science teachers' STEB. Pretest-posttest control group design was utilized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…The investigation of the relationship between teacher efficacy and knowledge about EBDs demonstrated a significant correlation between these constructs. Previous studies supported this relationship and reported that teachers with high levels of knowledge display high levels of efficacy, particularly in their teaching abilities (Goddard et al, 2004;Goker, 2021;Gümüş & Bellibaş, 2021;Guskey & Passaro, 1994;Kartal & Dilek, 2021;Latouche & Gascoigne, 2019;Li & Cheung, 2021;Lu et al, 2020;Oliver & Reschley, 2010;Rahmadani & Kurniawati, 2021;Sharma et al, 2012). Although previous studies addressed the relationship between these two constructs, the relationship between knowledge and efficacy was not investigated, specifically concerning working with students with EBDs.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the relationship between teacher efficacy and knowledge about EBDs demonstrated a significant correlation between these constructs. Previous studies supported this relationship and reported that teachers with high levels of knowledge display high levels of efficacy, particularly in their teaching abilities (Goddard et al, 2004;Goker, 2021;Gümüş & Bellibaş, 2021;Guskey & Passaro, 1994;Kartal & Dilek, 2021;Latouche & Gascoigne, 2019;Li & Cheung, 2021;Lu et al, 2020;Oliver & Reschley, 2010;Rahmadani & Kurniawati, 2021;Sharma et al, 2012). Although previous studies addressed the relationship between these two constructs, the relationship between knowledge and efficacy was not investigated, specifically concerning working with students with EBDs.…”
Section: Discussionmentioning
confidence: 99%
“…Some teachers might consider technology an essential component in effective science teaching. Kartal and Dilek (2021) found that a technology-supported teaching method course and microteaching promoted preservice teachers' science teaching efficacy beliefs. Similarly, preservice teachers reported that using technology promoted students' learning, and technology was a crucial constituent of effective science teaching (Min et al, 2020).…”
Section: Science Teaching Efficacy Beliefsmentioning
confidence: 98%
“…Teachers with a high level of science teaching efficacy are supposed to be open and willing to innovations, new teaching methods, and new ideas such as using instructional technologies (Blonder et al, 2013;Gagnier et al, 2021;Kartal & Dilek, 2021;Woolfolk-Hoy & Spero, 2005). Teachers' efficacy levels determine the effort they put on and the time they spent to achieve their teaching-related goals (Tschannen-Moran & Woolfolk-Hoy, 2001).…”
Section: Science Teaching Efficacy Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components are collaboration, authentic problems, applied projects, scaffolded feedback and reflection, and professionalization opportunities. For example, we include microteaching experiences in which pre-service teachers can apply lessons from our courses with students (Kartal & Dilek, 2021). These components work together and are centered around high-quality content, including science, math, and integrated STEM content noted above (Lewis et al, 2014).…”
Section: Thementioning
confidence: 99%